Development of Graphene Oxide/Polyaniline Inks for High Performance Flexible Microsupercapacitors via Extrusion Printing. (30th March 2018) - Liu, Yuqing; Zhang, Binbin; Xu, Qun; Hou, Yuyang; Seyedin, Shayan; Qin, Si; Wallace, Gordon G.; Beirne, Stephen; Razal, Joselito M.; Chen, Jun
Abstract: Extrusion printing of interdigitated electrodes for flexible microsupercapacitors (fMSCs) offers an attractive route to the fabrication of flexible devices where cost, scalability, and processability of ink formulations are critical. In this work, highly concentrated, viscous, and water‐dispersible inks are developed based on graphene oxide (GO)/polyaniline (PANi) composite for extrusion printing. The optimized GO/PANi‐based all‐solid‐state symmetric fMSCs obtained by extrusion printing interdigitated microelectrodes can deliver outstanding areal capacitance of 153.6 mF cm −2 and volumetric capacitance of 19.2 F cm −3 at 5 mV s −1 . It is shown that by fabricating asymmetric fMSCs using the GO/PANi as positive electrode and a graphene‐based negative electrode, the voltage window can be widened from 0.8 to 1.2 V and improvements can be achieved in energy density (from 3.36 to 4.83 mWh cm −3 ), power density (from 9.82 to 25.3 W cm −3 ), and cycling stability (from 75% to 100% capacitance retention over 5000 cycles) compared with the symmetric counterpart. The simple ink preparation and facile device fabrication protocols reported here make the scalable fabrication of extrusion printed fMSCs a promising technology. Abstract : A concentrated, viscous, and water‐dispersible ink comprised of graphene oxide/polyaniline hierarchical structure is facilely prepared with the stabilizer of poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonate) for extrusion printing. The printed symmetric microsupercapacitors can deliver outstanding areal and volumetric capacitance. The technique is also applicable to prepare asymmetric microsupercapacitors, which exhibit improved performance (i.e., energy, power densities, and cycling stability) than the symmetric ones.